Risk factors associated with the severity of injury outcome for paediatric road trauma. Issue 5 (May 2015) - Mitchell, R.J.; Bambach, M.R.; Foster, K.; Curtis, K.
Abstract Road trauma is one of the most common causes of injury for children. Yet risk factors associated with different levels of injury severity for childhood road trauma have not been examined in-depth. This study identifies crash and injury risk factors associated with the severity of non-fatal injury outcome for paediatric road trauma. A retrospective analysis was conducted of paediatric road trauma identified in linked police-reported and hospitalisation records during 1 January 2001 to 31 December 2011 in New South Wales (NSW), Australia. The linkage rate was 54%. Injury severity was calculated from diagnosis classifications in hospital records using the International Classification of Disease Injury Severity Score. Univariate and multi-variable logistic regression was conducted. There were 2412 car occupants, 1701 pedestrians and 612 pedal cyclists hospitalised where their hospital record linked to a police report. For car occupants, unauthorised vehicle drivers had twice the odds (OR: 2.21, 95%CI 1.47–3.34) and learner/provisional drivers had one and a half times higher odds (OR: 1.54, 95%CI 1.15–2.07) of a child car occupant sustaining a serious injury compared to a minor injury. For pedal cyclists and pedestrians, there were lower odds of a crash occurring during school commuting time and higher odds of a crash occurring during the weekend or on a dry road for children who sustained a serious versus a minor injury. Injury prevention initiatives, such as restraint and helmet use, that should reduce injury and/or crash severity are advocated.